2016
DOI: 10.17140/sbrpoj-1-104
|View full text |Cite
|
Sign up to set email alerts
|

The “I”s have it: Sex and Social Status Differences on Twitter

Abstract: We examined the use of "I" in Tweets posted by 50 famous people during a one-month window. The linguistic inquiry and word count (LIWC) was implemented to determine the percentage of 140-character Tweets that used the personal pronoun "I". Our findings showed patterns typically seen in natural speech. Specifically, women used the self-referent focus "I" significantly more often than men did, and lower status (operationalized as the number of Twitter followers) people used "I" significantly more often than thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Status may be more important than sex among this target sample, 21 particularly because the ages of persons in this sample is large compared to many language studies. While not all language studies focus on only college-aged language users 14,16 many LIWC studies focused on college-aged students, who may show more sex-linked language differences.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Status may be more important than sex among this target sample, 21 particularly because the ages of persons in this sample is large compared to many language studies. While not all language studies focus on only college-aged language users 14,16 many LIWC studies focused on college-aged students, who may show more sex-linked language differences.…”
Section: Discussionmentioning
confidence: 97%
“…20 Social status differences (such as those due to rank, hierarchy, or importance) are also important to language use, particularly pronoun use. 21,22 Less, however, is known about how status as opposed to other social and demographic markers influences affect language. While Kacewicz et al's 22 study of status focused on pronoun use, those researchers also reported no statistically significant overall effect sizes for affect collapsing across five studies in a meta-analysis.…”
Section: "I'm So Overwhelmed By All This Birthday Love!!!! Thank You mentioning
confidence: 99%
See 1 more Smart Citation
“…Each Instagram caption was taken verbatim from the post and placed into a word document, where we then applied the Linguistic Inquiry and Word Count 2015. 2 Following Beach et al 10 we used a median split of number of followers to delineate high and low status, and then used a 2×2 (Sex×Status Median Split) between-subjects ANOVA with number of followers as the dependent measure to check our manipulation. Table 1 shows the mean number of followers according to our independent variables.…”
Section: Methods Samplementioning
confidence: 99%
“…On Twitter, for example, women and lower-status persons used "I" in their Tweets, but "I" was equal (and lesser-likely) in both women and men of higher social status. 10 The use of an informal and friendly style that includes self-referencing is seen in men of lower social status, perhaps in effort to engage more people and enhance their own status through more self-referencing. The use of "I" signals a more "narrative" or "story-like" approach to provide perspective, omitting sophisticated language, and avoiding cognitive mechanisms.…”
Section: Introductionmentioning
confidence: 99%